Microtia reconstruction: our experiences of first 10 cases in Bangladesh (Bangladesh Journal of Plastic Surgery, 2011)
Varying degrees of congenital ear deformity (microtia) occurs 1 in about 8000 to 10,000 live births. One of the greatest challenges in plastic surgery is total auricular reconstruction as it demands precise technique as well as artistic creativity. In Bangladesh, recent advancement in the technique of carving and sculpting rib cartilage  and better training for achieving finer anatomic details has given a break through in the surgical management of  deformed ear. Between January 2009 and January 2010, total ear reconstruction was done with a two-stage method using  autogenous costal cartilage in the Department of Plastic Surgery, Dhaka Medical College Hospital, Dhaka. In the first stage, lobule rotation, fabrication of the cartilage framework and its implantation were performed. In  the second stage, elevation of the auricle and formation of the tragus were done. A total of 10 cases with microtia comprising different age group have been operated. All of them underwent stage I operation; among them 8 patients went through stage II procedure while the other 2 are waiting for the same. Results: 10 patients, ranging in age between 8 and 25 years, were operated on using autogenous costal cartilage between 2009 and 2010. Six patients were males and four were females. Unilateral microtia was present in all of these patients (7 right, 3 left). Eight cases were with Grade III microtia; the remaining 2 cases presented with Grade II microtia. The follow-up period was one month to one year. Seven among 8 cases presented acceptable ear contour after second stage ear reconstruction. The cranioauricular angle of the reconstructed ears was also similar to that of the opposite ears. Unfavourable result was deformation of the constructed helix which occurred in one case. Though it is impossible to reconstruct an ear that appears exactly as the opposite one, the new ears which were  made were of correct size and in normal position with impressive finer three dimensional details that achieved patients satisfaction as well as surgeons professional gratification.Key words: Microtia; Two stage auricular reconstruction; Autologous costochondral cartilageBDJPS 2010; 1(2): 14-19